Detailed in-furnace measurements in a pulverized coal-fired furnace with combined woody biomass co-firing and air staging - Choi, Minsung; Li, Xinzhuo; Kim, Kibeom; Sung, Yonmo; Choi, Gyungmin (Journal of mechanical science and technology, 2018)
This paper presents a detailed experimental description of the combined effects of woody biomass co-firing and air staging on NO emissions and burnout performance in a pulverized coal-fired furnace. The co-combustion of woody biomass and bituminous coal was evaluated using woody biomass co-firing proportions of 0 % to 30 % with intervals of 10 %. Detailed in-furnace gas temperature and gas-phase concentration for species such as O 2 , CO 2 , CO and NO were measured for the co-firing flames, both with and without air staging. The overall temperature of the woody biomass co-firing flames was higher than that of the pure bituminous coal flame. This effect was more pronounced for air-staged combustion than for combustion without air staging. Co-firing woody biomass with air staging strongly affected NO reduction efficiency, whereas NO emissions were insignificant for no-staged firing. The deteriorating effect of air staging on burnout performance was a function of the woody biomass co-firing ratio. NO reduction efficiency for the air-staged flames was improved by more than 40 % in both flames for woody biomass co-firing proportions of 10 % and 20 %.